2009
DOI: 10.1124/jpet.109.152470
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Long-Acting Muscarinic Antagonists: Comparison of Tiotropium and Investigational Drugs

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by progressive airflow limitation caused by persistent inflammatory processes in the airways. An increased cholinergic tone mediates different pathophysiological features of COPD, such as bronchoconstriction and mucus hypersecretion, mostly through activation of the human muscarinic M 3 receptor (hM 3 ) subtype. Tiotropium bromide (Spiriva) is a well established muscarinic antagonist in the pharmacological management of COPD with a once-daily posolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 25 publications
7
141
1
6
Order By: Relevance
“…The observed difference in the changes (extent, duration) in binding parameters (K d , B max ) after the intratracheal administration of tiotropium, ipratropium, and glycopyrrolate (Tables 3, 4) seems to coincide with the functional and in vitro receptor binding characteristics. In fact, Casarosa et al (37) showed that intratracheal tiotropium induced considerable bronchoprotection in anesthetized dogs lasting more than 24 h, significantly longer than glycopyrrolate. Both in the recovery of carbachol-induced contraction of the isolated guinea-pig tracheum and in the offset of the bronchodilator effects of anticholinergic agents in the isolated human bronchus, the glycopyrrolate-induced bronchodilation lasted longer than the ipratropium, but not tiotropium, -induced bronchodilation (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed difference in the changes (extent, duration) in binding parameters (K d , B max ) after the intratracheal administration of tiotropium, ipratropium, and glycopyrrolate (Tables 3, 4) seems to coincide with the functional and in vitro receptor binding characteristics. In fact, Casarosa et al (37) showed that intratracheal tiotropium induced considerable bronchoprotection in anesthetized dogs lasting more than 24 h, significantly longer than glycopyrrolate. Both in the recovery of carbachol-induced contraction of the isolated guinea-pig tracheum and in the offset of the bronchodilator effects of anticholinergic agents in the isolated human bronchus, the glycopyrrolate-induced bronchodilation lasted longer than the ipratropium, but not tiotropium, -induced bronchodilation (36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Haddad et al (19) showed that the inhibition by glycopyrrolate of electrical field stimulation-induced contraction of guinea-pig trachea and human airways was significantly more prolonged than that by ipratropium. In relation to the in vitro receptor binding kinetics, Casarosa et al (37) showed that the dissociation half-life (t 1/2 ) from the human M 3 receptor of tiotropium (27 h) was much longer than that of glycopyrrolate (6.1 h). Also, it was reported that glycopyrrolate compared with ipratropium dissociated more slowly from muscarinic receptors in human airway smooth muscle (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although blocking M 1 /M 3 receptor subtypes would counteract airway limitation in chronic obstructive pulmonary disease patients, blocking presynaptic M 2 autoreceptors would be detrimental for this purpose and systemic M 2 antagonism would increase the risk of tachycardia as side effect. The difficulties in finding muscarinic receptor subtype-selective ligands were successfully overcome by the development of ipratropium, a shortacting muscarinic antagonist, and long-acting muscarinic antagonists (LAMAs) tiotropium (Disse et al, 1993) and the novel aclidinium (Gavaldà et al, 2009) and glycopyrronium (Casarosa et al, 2009) that are particularly indicated for maintenance therapy. All these drugs dissociate more rapidly from M 2 than from M 3 receptors.…”
Section: Examples For Biologic Discrimination By Different Ligand Resmentioning
confidence: 99%
“…All these drugs dissociate more rapidly from M 2 than from M 3 receptors. Apart from the advantageous kinetic subtype selectivity of these drugs, the duration of action of the LAMAs was suggested to be primarily related to their long residence time at M 3 receptors (Disse et al, 1993;Casarosa et al, 2009). Hence, it was shown that the duration of the bronchodilator action in vivo of different muscarinic antagonists resembles their residence times at M 3 receptors determined in vitro under nonphysiologic conditions (Gavaldà et al, 2014).…”
Section: Examples For Biologic Discrimination By Different Ligand Resmentioning
confidence: 99%
“…Az M3-ról a disszociáció felezési ideje tiotropiumnál 27 óra, aclidiumnál 10,7 óra, glycopirrhoniumnál 6,1 óra. Az M2-ről a disszociáció felezési ideje tiotropiumnál 2,6 óra, aclidiniumnál 1,8 óra, glycopirrhoniumnál 0,37 óra [45,53,54,55,56,57].…”
Section: Következtetésekunclassified